Ketamine for rapid control of hyperactive delirium with severe agitation. A retrospective comparison study - Beatrice Borreani; Annalisa Belluti; Francescopaolo D'Adamo; Luca Acquarone; Cristina Cocino; Paolo Canepa; Francesco Quaglia; Martina D'Antoni; Andrea Alienda; Alessandro Riccardi (JEM Reports)
Background: The agitated patient represents a very large clinical problem for the work of the emergency department. The therapeutic goal is rapid symptom control while ensuring maximum patient safety. Hyperactive delirium constitutes a true clinical emergency, and some sedatives carry inherent risks. Ketamine has already demonstrated remarkable safety in this setting. OBJECTIVES This study aims to indentify an effective and safe option for the rapid control of severe psychomotor agitation METHODS Our retrospective study analyzes the comparison of ketamine alone, ketamine with droperidol, and midazolam with haloperidol. RESULTS During the period of January 2022 and September 2023 we identified 66 patients with severe psychomotor agitation (13–76 years), and we demonstrated a faster and more effective response in patients treated with ketamine, and a reduction in adverse events in patients treated with ketamine and droperidol. CONCLUSIONS Our data show that patients treated with ketamine exhibit a significantly faster response, with immediate patient control, with greater safety than patients treated with midazolam. The combination with droperidol increases clinical efficacy compared with ketamine alone.